1978
DOI: 10.1037/0021-9010.63.6.728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of attention, as indexed by subsequent memory, on electrodermal detection of information.

Abstract: Three closely related experiments tested the effects of attention, as indexed by subsequent memory, on electrodermal detection of information. A total of 62 male college students attempted to conceal six critical items of information from a polygraph examiner recording their electrodermal response (EDR). In the polygraph test the subject was asked if any of a list of 24 words, one every 10-15 sec, were critical items he was concealing. The list was comprised of three semantically similar control words along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
(13 reference statements)
6
20
0
Order By: Relevance
“…Less elaborated items were accurately detected after 10 min, but by 1 week test accuracy was significantly compromised. In previous CKT studies, test accuracy was affected by test delay in some cases (Rosenfeld et al 1991 ; Waid et al 1978 , 1981 a), but not in others (Carmel et al 2003 ). The present data suggest that this discrepancy may have been driven by differences in probe elaboration.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Less elaborated items were accurately detected after 10 min, but by 1 week test accuracy was significantly compromised. In previous CKT studies, test accuracy was affected by test delay in some cases (Rosenfeld et al 1991 ; Waid et al 1978 , 1981 a), but not in others (Carmel et al 2003 ). The present data suggest that this discrepancy may have been driven by differences in probe elaboration.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have demonstrated that the amount of attention paid to a particular crime item is positively correlated with both the level of physiological response to that item during a lie test, as well as to the item’s later explicit recall by the participant. In these studies, level of attention was not manipulated, but inferred by the level of physiological response to each stimulus during study (e.g., Waid et al 1978 , 1981 a). This correlation between attention and detectability appears to predict that using peripheral items in the CKT will lead to poorer detection efficiency than more central items.…”
Section: Introductionmentioning
confidence: 99%
“…Research demonstrating positive correlations between OR and later recall of the stimulus material supports this view (e.g., Corteen, 1969 ). Indeed, several CIT studies found a positive association between recall and detection efficiency (e.g., Waid et al, 1978 , 1981b ; Iacono et al, 1984 ; Carmel et al, 2003 ; Verschuere et al, 2007 ).…”
Section: The Theoretical Foundation Of the Citmentioning
confidence: 99%
“…Disrupted attention would have attenuated responding to relevant items among the guilty, thereby degrading test performance. Although attention could not be measured directly, it was inferred from subsequent memory for test items in a paradigm similar to that performed by Waid et al (1978). Neither the recall test nor the recognition test showed a difference in terms of testing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature effects on cognition were a potential confound during testing. With the CIT questioning method, classification accuracy will be lower for guilty persons who pay less attention during the polygraph examination (Waid, Orne, Cook, & Orne, 1978). This finding is important, as both high and low ambient temperatures can impair an individual's attention (M€ akinen, 2007;Pilcher, Nadler, & Busch, 2002).…”
mentioning
confidence: 99%